Are leaders responsible for meaningful work?: perspectives from Buddhist-enacted leaders and Buddhist ethics - Vu, Mai Chi (Journal of business ethics, 2023)
The literature on meaningful work often highlights the role of leaders in creating a sense of meaning in the work or tasks that their staff or followers carry out. However, a fundamental question arises about whether or not leaders are morally responsible for providing meaningful work when perceptions of what is meaningful may differ between leaders and followers. Drawing on Buddhist ethics and interviews with thirty-eight leaders in Vietnam who practise "engaged Buddhism" in their leadership, we explore how leaders understand their roles in creating meaningfulness at work and their perceptions of how employees experience their leadership approach in this respect. On the basis of Buddhist ontology on the sense of meaningfulness, we introduce a number of leadership approaches in cultivating meaning at work that question the argument that leaders are primarily responsible for enabling or satisfying employees' search for meaning. The study provides an alternative lens through which to examine the role of leadership from a Buddhist ethics perspective and shows how an insight from this particular tradition can enrich secular interpretations of meaningful work and leadership.